Perfluorobutane CEUS for early-stage cervical lymphoma: diagnostic value of the postvascular phase starfield sign - Liang, Xia; Zeng, Xian-Tao; Hong, Zhi-Liang; Lin, Xiao-Ying; Su, Miao-jiao; Yang, Jian-Chuan; Wu, Song-Song (Scientific reports, 2025)
Early differentiation of cervical lymphoma from benign lymphadenopathy remains challenging on conventional imaging. This study assesses the diagnostic efficacy of perfluorobutane contrast-enhanced ultrasound (CEUS) in differentiating early-stage cervical lymphoma from benign lymph nodes (LNs). From November 2023 to January 2025 we prospectively enrolled patients suspected of having cervical lymphoma based on ultrasound (US) findings and scheduled for LN biopsy. All patients underwent CEUS to evaluate LN vascular (5–60 s post-injection) and postvascular (10–30 min post-injection) phases before biopsy. Histopathology served as the reference standard. Diagnostic performance metrics, including sensitivity, specificity, and accuracy, were calculated. Logistic regression analyzed the area under the receiver operating characteristic curve (AUC) for US, CEUS, and combined features. Forty-seven LNs (23 lymphomas, 24 benign) were analyzed. The sensitivity of the postvascular phase starfield sign was 91.30%, specificity was 83.33%, positive predictive value was 84.00%, negative predictive value was 90.91%, and the AUC was 0.87 (95% CI 0.76–0.98). The AUC for CEUS was 0.89 (95% CI 0.79–1.00), and the AUC for the combination of postvascular phase and US features was 0.92 (95% CI 0.82–1.00), significantly higher than that for US features alone (AUC, 0.68; 95% CI 0.53–0.84; P < 0.05). Perflubutane CEUS can effectively distinguish between cervical lymphoma and benign LNs. The postvascular phase starfield sign demonstrates significant diagnostic efficacy and could improve clinical management strategies.